A qualitative study of collaborative stimulation in group design thinking. (5th April 2016) - Sauder, Jonathan; Jin, Yan
Abstract : It is often assumed in both education and industry that collaboration encourages creativity. This assumption is explored by investigating the influence of designers' interactions on creativity-relevant thinking processes by extending creative cognition to the group design context. It is proposed that sharing design entities and questions stimulates creativity-relevant thinking processes through four types of collaborative stimulation. Specific patterns are hypothesized to exist between each type of collaborative stimulation and thinking processes. A case study was conducted to determine whether the hypothesized types and patterns of collaborative stimulation exist. The results were analyzed using a directed coding approach and collaborative retrospective protocol analysis, which enable capturing both internal thoughts and external interactions with minimal interference to collaboration. The results indicate that the identified types of collaborative stimulation are observable and that they have recognizable patterns with stimulated thinking processes. Stimulation occurring through design entity questioning had the strongest relationship with generative thinking processes. Although creativity-relevant generative processes are stimulated by collaborative activity, this does not necessarily mean that collaboration results in a more creative product. However, these patterns can be used in future work to develop methods and interventions for promoting group idea generation and improving group creativity.